Media Sosial Sebagai Media Pembelajaran Bagi Generasi Z - Andrias Pujiono (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
This study aims to see whether social media can be used as one of the relevant learning media for Generation Z. This is driven by the fact that social media is a media that is closely related to generation Z children. In this study, researchers used the library research method. In this method, the researcher examines various relevant and reliable sources related to the characteristics and use of social media as a learning medium. From the research that has been done, it appears that social media meets the criteria as a learning medium. Service features in various social media can be used as a medium that bridges or simplifies the learning process. With social media, teachers and students can interact in a learning activity, anywhere and anytime, not limited to space and time. The use of social media is very relevant for generation Z.